Typology of Cajanus cajan cultivation systems in Benin, West Africa - Akpo, Ibidon Firmin; Tassou Zakari, Filikibirou; Houessingbe, Zachée; Yabi, Afouda Jacob (Journal of Agriculture and Environment for International Development (JAEID), 2025)
Pigeon pea farms are heterogeneous, applying varied cropping systems. In this context, the study of the typology of farms taking into account the cropping systems they adopt is of practical importance for the implementation of targeted and effective technological interventions. The objective of this research is to identify and characterize the pigeon pea cropping systems practiced in Central Benin. A field survey was conducted among 240 pigeon pea producers randomly selected in the communes of Bantè, Glazoué and Ouèssè. Principal Component Analysis (PCA), Chi-square test of independence, analysis of variance (ANOVA) and multinomial logit regression were used to analyze the collected data. Three types of cropping systems were identified. The first system, adopted by 31.25% of farmers, is characterized by pure stand cultivation, the use of herbicides and a reduced frequency of manual weeding. The second system, chosen by 47.08% of participants, is characterized by mixed cultivation with maize, legumes (soybean, peanut), or other crops (cassava, yam, market garden crops and sometimes in cashew plantations), without the use of herbicides but with a moderate frequency of manual weeding. The third system, adopted by 21.67% of farmers, is characterized by mixed cultivation with maize, the use of herbicides and a limited frequency of manual weeding. These systems have varying levels of economic performance and appear to be specific to each municipality. Factors such as available agricultural area, Mahi ethnicity, and location within the Glazoué and Ouèssè communes significantly influence the choice of these systems. The results advocate for promoting pure stand systems and improved varieties to optimize yields across all cultivation systems.